Effects of UV-A Light Treatment on Ammonia, Hydrogen Sulfide, Greenhouse Gases, and Ozone in Simulated Poultry Barn Conditions - Myeongseong Lee; Jisoo Wi; Jacek A. Koziel; Heekwon Ahn; Peiyang Li; Baitong Chen; Zhanibek Meiirkhanuly; Chumki Banik; William Jenks (Atmosphere, 2020)
Gaseous emissions, a side effect of livestock and poultry production, need to be mitigated to improve sustainability. Emissions of ammonia (NH3), hydrogen sulfide (H2S), greenhouse gases (GHGs), and odorous volatile organic compounds (VOCs) have a detrimental effect on the environment, climate, and quality of life in rural communities. We are building on previous research to bring advanced oxidation technologies from the lab to the farm. To date, we have shown that ultraviolet A (UV-A) has the potential to mitigate selected odorous gases and GHGs in the context of swine production. Much less research on emissions mitigation has been conducted in the context of poultry production. Thus, the study objective was to investigate whether the UV-A can mitigate NH3, H2S, GHGs, and O3 in the simulated poultry barn environment. The effects of several variables were tested: the presence of photocatalyst, relative humidity, treatment time, and dust accumulation under two different light intensities (facilitated with fluorescent and light-emitting diode, LED, lamps). The results provide evidence that photocatalysis with TiO2 coating and UV-A light can reduce gas concentrations of NH3, CO2, N2O, and O3, without a significant effect on H2S and CH4. The particular % reduction depends on the presence of photocatalysts, relative humidity (RH), light type (intensity), treatment time, and dust accumulation on the photocatalyst surface. In the case of NH3, the reduction varied from 2.6−18.7% and was affected by RH and light intensity. The % reduction of NH3 was the highest at 12% RH and increased with treatment time and light intensity. The % reduction of NH3 decreased with the accumulation of poultry dust. The % reduction for H2S had no statistical difference under any experimental conditions. The proposed treatment of NH3 and H2S was evaluated for a potential impact on important ambient air quality parameters, the possibility of simultaneously mitigating or generating GHGs. There was no statistically significant change in CH4 concentrations under any experimental conditions. CO2 was reduced at 3.8%−4.4%. N2O and O3 concentrations were reduced by both direct photolysis and photocatalysis, with the latter having greater % reductions. As much as 6.9−12.2% of the statistically-significant mitigation of N2O was observed. The % reduction for O3 ranged from 12.4−48.4%. The results warrant scaling up to a pilot-scale where the technology could be evaluated with economic analyses.